(untitled) (Palíndromo, 2026)
This is a visual essay, a textual-visual practice that is also part of the documentary archive of a performance. This work revisits the action undertaken by Claude Cahun and Marcel Moore to halt the advance of fascism and stop the war. The two artist-activists-lovers were convicted of "using spiritual weapons": words. The essay explores this pacifist-mutant-dreamlike-militant-queer action, to which art narratives initially gave less attention.